THE CIS COUNTRIES: SOME PECULIARITIES OF ECONOMIC DEVELOPMENT - BUDKIN, Viktor (CENTRAL ASIA AND THE CAUCASUS, 2012)
December 1991 marked the beginning of a grandiose experiment whose purpose was to establish a whole group of independent states in the territory of a world giant known as the U.S.S.R., which occupied one-sixth of the Earth. Their establishment was based on the negation of the previous Soviet model providing for the domination of one party, which had im-posed a no-choice ideology on the society, and for the administrative command system of politics and economics. Could that experiment succeed? Certainly, especially given the successes of the countries of Central Europe (CE) and the Baltic region. Unfortunately, the path of social reform chosen by the post-Soviet countries has never actually demonstrated its effectiveness in the past two decades. The imitation of democratic reforms led to a state of affairs where most of the population in the post-Soviet states was barred from having real influence on political processes, which are now based on the activities of clan groups. Denationalization and privatization have resulted in very high-income inequality in the society, i.e. its di-vision into a small group of super-rich oligarchs and the majority of the people with low or middle incomes (sometimes slightly higher). There is no denying that the newly independent states (NIS) have made some progress in regaining their national identity and restoring respect for traditional customs and religion. Meanwhile, these successes could have been more significant had they been supported by the dynamic development of the economic base of the Commonwealth of Independent States (CIS)countries. The following analysis shows that the economy is the weakest link in the process of enhancing stability in the CIS countries, and this has a negative effect on both the internal situation in the NIS and their position in the world community.